Perceived Individual Team Member Value Creation in In-Class Permanent Teams. Analysis of evidence from individual peer reviews in a Team-Lecture Hybrid instructional strategy. - David Tataw (Journal of the Scholarship of Teaching and Learning)
This study analyzes individual peer review assessment data in order to understand the following: contributions of  individual team members to in-class  permanent  team  outcomes; social loafing and loss of social interdependence among team members; and the achievement  of the Team Lecture Hybrid(TLH) instructional strategy learning outcomes in a team learning environment. A value creation theoretical framework was used to  assess perceived value creation in 952 statements recorded in 341 intra-group assessment narratives from 127 students in 28 in-class permanent teams across 11 courses. Participants were drawn from public affairs, leadership, and healthcare administration courses, in two US institutions of higher learning from January 2012 to May 2016. Fifteen emerging  themes organized under four predetermined domains including preparednesss (14.3%), contribution to productivity (53.4%), respect for others (13.8%), and flexibility (18.1%; and one emergent domain including teacher contribution (1.15%); revealed the following about individual performance: 1. either added to, or subtracted from collective team performance; 2. were empirically aligned with four value creation cycles in the value creation conceptual framework; and 3.  advanced four expected student learning outcomes. Social loafing and loss of social interdependence was identified in team member interactions and they interfere with student learning outcomes. Permanent team members desired and expected the following five attributes from their team members: 1. to be prepared for project activities; 2. to contribute substantially or intangibly to team productivity by sharing knowledge, having good work habits, improving the team product, and helping with leadership and coordination; 3. to be respectful of others;4. to seek consensus and comprise; and  5. to show flexibility in their interaction with others They also see their teacher as an intangible resource in the permanent team who provides knowledge, moral leadership, structure, and mentoring. Instructors and student should consider these findings when they participate or facilitate learning activities in in-class permanent teams.